Comparative Effectiveness of KDIGO 2021 versus Previous Blood Pressure Targets on Renal Outcomes in Chronic Kidney Disease Patients in Palembang, Indonesia - Jonah Abraham; Andhika Kurnianta Kusuma (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: The 2021 Kidney Disease: Improving Global Outcomes (KDIGO) guidelines recommend lower blood pressure (BP) targets for chronic kidney disease (CKD) patients compared to previous guidelines. This study aimed to evaluate the comparative effectiveness of achieving KDIGO 2021 BP targets versus previous targets on renal outcomes in CKD patients in Palembang, Indonesia. Methods: A retrospective cohort study was conducted involving CKD patients (stages 1-5, not on dialysis) attending a tertiary hospital in Palembang from January 2018 to December 2023. Patients were categorized into two groups: those achieving KDIGO 2021 BP targets (<120/80 mmHg) and those achieving previous targets (<130/80 mmHg). The primary outcome was a composite of renal events including a 50% decline in estimated glomerular filtration rate (eGFR), end-stage renal disease (ESRD), or renal death. Secondary outcomes included individual components of the composite outcome and all-cause mortality. Data were analyzed using Kaplan-Meier survival analysis and Cox proportional hazards regression. Results: A total of 860 CKD patients were included (mean age 58.2 ± 12.5 years, 52% male). 345 patients achieved KDIGO 2021 BP targets, while 515 achieved previous targets. Over a median follow-up of 3.8 years, the primary composite outcome occurred in 187 patients (21.7%). The incidence rate of the primary outcome was significantly lower in the KDIGO 2021 group (15.6 per 1000 person-years) compared to the previous targets group (27.2 per 1000 person-years) (p=0.003). After adjusting for potential confounders, achieving KDIGO 2021 BP targets was independently associated with a lower risk of the primary outcome (hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.38-0.83, p=0.004). Similar findings were observed for individual components of the composite outcome and all-cause mortality. Conclusion: Achieving KDIGO 2021 BP targets was associated with a significant reduction in the risk of adverse renal outcomes and all-cause mortality in CKD patients in Palembang. These findings support the implementation of the updated KDIGO guidelines in this population.